Proceedings of the 7th International Conference on Education, Management, Information and Mechanical Engineering (EMIM 2017) 2017
DOI: 10.2991/emim-17.2017.44
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Porosity and Permeability on Invasion Depth During Drilling Mud-filtrate Invading into a Reservoir Dynamically

Abstract: Abstract. The drilling mud-filtrate invades into a reservoir is a dynamical process after a formation was opened in oil exploration. Since the invasion profiles of formation resistivity vary with time, the invasion depth is related to time. The fluid flow equations were used to calculate the invasion profiles and invasion depth. The present dynamic invasion model generated the time-dependent formation resistivity profiles and invasion depth. The effects of two main parameters, porosity and permeability, for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…showed that, at higher porosities and permeabilities, the invasion depth of filtrated mud had increased, which was also indicated in the results of this model [32].…”
Section: Porosity Effectsupporting
confidence: 77%
See 1 more Smart Citation
“…showed that, at higher porosities and permeabilities, the invasion depth of filtrated mud had increased, which was also indicated in the results of this model [32].…”
Section: Porosity Effectsupporting
confidence: 77%
“…(2017) investigated the profound impact of porosity and permeability on the filtrated invasion depth as a numerical model. His findings showed that, at higher porosities and permeabilities, the invasion depth of filtrated mud had increased, which was also indicated in the results of this model [32].…”
Section: Porosity Effectsupporting
confidence: 67%
“…It is desirable to design a mud slurry which will give low permeable mud cakes which indicates good filterability. Relatively, smaller grain particles give good filtration properties because their compacted structure offers less permeability which improves the filtration behaviour (Zhang 2017). Moreover, the filtration behaviour of drilling mud is strongly controlled by its ability to flocculate, dispersed and deflocculated.…”
Section: Mechanism Behind Improvement In Filtration Propertiesmentioning
confidence: 99%
“…In this paper, when studying the distribution law of pollution radius, various forms of radius distribution of pollution zone are considered (as shown in Figure 7), and the empirical equation and oscillation decreasing function of wellbore pollution radius are combined. Ling et al (2015); Fan et al (2017); Zhang (2017) and others obtained the model of drilling fluid invasion depth in horizontal wells by multiple regression processing of experimental data. Based on the research (Jiang et al, 2023), the distribution law of the radius of the contaminated zone along the vertical direction of the wellbore is given as follows:…”
Section: Pollution Radius Distribution Modelmentioning
confidence: 99%